Systematic Literature Review of System Engineering Design Methods - Sales, Diego C.; Becker, Leandro Buss (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2018)
This paper provides a systematic literature review of System Engineering (SE) design methods, SE standards, process models, and its employment in Model-Based System Engineering (MBSE). Currently, there are three major standards being applied to non-defense domain, covering different levels of details related to a system's life cycle. It also details other related standards and guidelines that have focused in different features. Given that the choice of which standard to adopt in a certain project is a challenge, this paper presents some elements that might help designers making the appropriate choice. A paradigm about MBSE methodologies and traditional SE process document-based is related, and it can be anticipated that conclusions goes towards using MBSE and multi-standards in SE projects.